(untitled) (Journal of Nepal Geological Society, 2000)
In drought-prone and semiarid areas, the groundwater table is deep and the soils are at an unsaturated state because of evaporation or transpiration. The negative pore water pressure or matric suction (ua-uw) is an important property of unsaturated soils that are situated above the groundwater table. In the conditions of rainfall, ground seepage, or drainpipe leakage, the matric suction will decrease with the increase of the degree of saturation, and the soils will lose their part of shear strength, which is the main reason why many unsaturated soil slopes become unstable. This paper discusses the engineering properties of unsaturated soils. Following the limit equilibrium principle, the unsaturated soil slopes are evaluated by applying the slice method.